Abnormal oculocardiac reflex in two patients with Marcus Gunn syndrome - Maitree Pandey; Neha Baduni; Aruna Jain; Manoj Kumar Sanwal; Homay Vajifdar (Wolters Kluwer Medknow Publications, 2011)
Marcus Gunn phenomenon is seen in 4 to 6% of congenital ptosis patients. We report two cases of abnormal oculocardiac reflex during ptosis correction surgery. Marcus Gunn syndrome is an autosomal dominant condition with incomplete penetrance. It is believed to be a neural misdirection syndrome in which fibres of the motor division of the trigeminal nerve are congenitally misdirected into the superior pterygoid and the levator muscles. Anesthetic considerations include taking a detailed history about any previous anaesthetic exposure and any reaction to it as this syndrome has a high probability of being associated with malignant hyperthermia. It is also postulated that an atypical oculocardiac reflex might be initiated in these patients as seen in our patients, so precautions must be taken for its prevention and early detection.